Viñas patrimoniales en Chile:: la corriente principal - Pszczolkowski, Philippo; Rojas, Gonzalo; Lacoste, Pablo (OS. Opificio della Storia, 2021)
This article examines the mainstream of heritage vineyards in Chile. The main characteristics of these vineyards and their territorial location are investigated. Methodologically, quantitative and qualitative sources have been used. A critical analysis of the Wine Registry has been carried out, in the light of specialized literature, together with field visits and taking as reference the vineyard censuses prepared in Argentina. It is concluded that the main current of the patrimonial vineyards of Chile is in the southern interior dry land secano, between the Mataquito and Bio Bio rivers; and is characterized by water regime without irrigation; the leading system Gobelet and the Spanish-Creole varieties, Listán Prieto, Moscatel de Alejandría and Torontel. The current area comprises 15,000 hectares concentrated in nine communes in three regions, Maule, Ñuble and Bio Bio. There is the heart of the patrimonial vineyards of Chile.